Già sono quattordici anni ne’ quali […] ogni anno vado visitando questi bagni d’Ischia - de Angelis, Teofilo (Kritik. Rivista di letteratura e critica culturale, 2024)
In 1588, Giulio Iasolino published De’ rimedi naturali che sono nell’isola di Pithecusa; hoggi detta Ischia, a balneotherapy work dedicated to the enhancement and promotion of the island’s thermal baths. This study demonstrates that the physician-author navigates seamlessly between tradition and innovation. On one hand, his profound knowledge of the medical-thermal genre, whose origins are attributed to Pietro da Eboli (c. 1160-c. 1220), is well-established. On the other hand, Iasolino is the first author to address this subject in vulgar, breaking with the exclusively Latin tradition that had characterized it until then.